Single-Point Linkage Engineering in Conjugated Phthalocyanine-Based Covalent Organic Frameworks for Electrochemical CO2 Reduction - Chen, Wenchang; Zhang, Yi; Yang, Mingyu; Yang, Chao; Meng, Zheng (Nano-Micro Letters, 2025)
The utilization of covalent organic frameworks (COFs) holds great potential for achieving tailorable tuning of catalytic performance through bottom-up modulation of the reticular structure. In this work, we show that a single-point structural alteration in the linkage within a nickel phthalocyanine (NiPc)-based series effectively modulates the catalytic performance of the COFs in electrochemical CO2 reduction reaction (CO2RR). A NiPc-based COF series with three members which possess the same NiPc unit but different linkages, including piperazine, dioxin, and dithiine, have been constructed by nucleophilic aromatic substitution reaction between octafluorophthalocyanine nickel and tetrasubstituted benzene linkers with different bridging groups. Among these COFs, the dioxin-linked COF showed the best activity of CO2RR with a current density of CO (jCO) = − 27.99 mA cm−2 at − 1.0 V (versus reversible hydrogen electrode, RHE), while the COF with piperazine linkage demonstrated an excellent selectivity of Faradaic efficiency for CO (FECO) up to 90.7% at a pretty low overpotential of 0.39 V. In addition, both a high FECO value close to 100% and a reasonable jCO of − 8.20 mA cm–2 at the potential of − 0.8 V (versus RHE) were obtained by the piperazine-linked COF, making it one of the most competitive candidates among COF-based materials. Mechanistic studies exhibited that single-point structural alteration could tailor the electron density in Ni sites and alter the interaction between the active sites and the key intermediates adsorbed and desorbed, thereby tuning the electrochemical performance during CO2RR process. Highlights: 1 Three novel covalent organic frameworks (COFs) composed of nickel phthalocyanine units and different linkages, including dioxin, piperazine, and dithiine, were successfully constructed. 2 It was found that only a single-point structural variation of the linkage in the COFs could effectively modulate their performance in CO2 reduction reaction, where the piperazine-linked COF achieved a pretty high Faradaic efficiency for CO of 90.7% at a critically low overpotential of 0.39 V. 3 Theoretical calculations indicated that the COF with dioxin linkage stabilized the *COOH intermediate more effectively than the other two NiPc-based COFs.